An Experimental Evaluation of the Weathering Effects on Mine Shaft Lining Materials - W. Yang; A. M. Marshall; D. Wanatowski; L. R. Stace (Advances in Materials Science and Engineering)
Many shaft collapses are related to the deterioration and failure of the masonry shaft lining materials. In modern mine shaft, concrete is widely used to provide support. To analyse shafts stability, the properties of the lining need to be well defined. The behaviour of masonry and concrete can be considerably affected by long-term exposure to harsh mine water. This paper presents a study which focuses on the weathering effects of mine water on lining materials (brick, mortar, and concrete). To reproduce the weathering process, samples were placed into solutions of potable water, artificial mine water, and a more aggressive mine-water solution for just less than one year. Four phases of laboratory tests were conducted throughout the time period to assess the degradation of mechanical properties of the lining materials. Particular attention is given to the degradation of material strength and stiffness. Results indicate that the harsh acidic mine water has pronounced detrimental effects on the strength and stiffness of mortar. The weathering process is shown to have the most significant effect on the stiffness of concrete and mortar. It is also shown that the use of mass loss as an index for evaluation of mechanical properties may not be appropriate.